Scientific Production on Venezuelan Migration: A Bibliometric Analysis - Cuéllar-Sánchez, Diana Mireya; Núñez-Valdés, Karen; Dueñas-Peña, Alex (Migration Letters, 2023)
The International Organization for Migration adheres to the notion that migration involves the displacement of individuals from one place to another, whether temporarily or permanently, whether voluntarily or forcibly, across international borders or within a country, and that these movements generate significant impacts on both the societies of origin and destination, as well as on the migrants themselves. This study focuses on a documentary review aimed at addressing the following questions: How is migration research approached in different countries? What is the volume of scientific production on this subject? Within the aforementioned context, the present work encompasses various types of documents published between 2012 and 2022, authored in English, and disseminated through the SCOPUS database. To undertake the analysis, a combination of tools such as VOSviewer, Biblioshiny, and Excel was employed. These tools facilitated the identification of clusters, co-occurrence frequencies, and nodes within the network. From the bibliometric analysis of Venezuelan migration, key years of high citation impact stand out, despite a relatively lower output of articles, thereby underscoring the principle of quality over quantity. The leadership of the United States, Colombia, and Venezuela in publications underscores their interest and relevance in this domain. Global scientific cooperation and the Bradford Law reveal patterns of thematic concentration within journals, influenced by prestige and preferences.